Fungal Population of Nutmeg (Myristica fragrans) Kernels Affected by Water Activity During Storage - Kiki Nurtjahja; Okky Setyawati Dharmaputra; Winiati Pudji Rahayu; Rizal Syarief (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2017)
The aim of this investigation was to determine the effect of various water activities (aw) on fungal population in nutmeg kernels during storage. The seed nutmegs were obtained from ripe fruits one week after they fell on the ground in North Minahasa Regency, North Sulawesi Province, Indonesia. The kernels (moisture content ± 10%) were stored 0, 15, and 30 days in various aw (0.75, 0.80, 0.83, 0.90, 0.97) using saturated salt solutions at 29 °C in sorption containers. Serial dilution method followed by a pour-plate method in Dichloran 18% Glycerol Agar (DG18) was used to isolate and quantify the fungal population. Results revealed that kernels stored at aw = 0.75 was not significantly (p < 0.05) different from at aw = 0.80-0.83. Fungal population of kernels determined aw and significantly (p < 0.05) influenced by duration of storage. Range of aw 0.80-0.83 has a smaller total fungal population than aw ≥ 0.90. Thirteen different genera/species were isolated and identified including Aspergillus and Eurotium (6 species), Penicillium (3 species), Fusarium (2 species), 1 species each of Cladosporium or Syncephalastrum, and isolate A. The largest total fungal population (5.0×105 CFU g-1) was present at the beginning of storage (aw = 0.97) and it was dominated by Penicillium citrinum (2.6×105 CFU g-1) followed by Cladosporium cladosporioides (1.7×105 CFU g-1). After 30 days of storage (aw = 0.97) the population of P. citrinum was still dominant with a population of 2.4×104 CFU g-1. Eurotium chevalieri followed with a population of 1.2×104 CFU g-1.